2015
DOI: 10.1186/s12879-015-1249-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating HBsAg rapid test performance for different biological samples from low and high infection rate settings & populations

Abstract: BackgroundRapid tests (RTs) might have several advantages over standard laboratory procedures, increasing access to diagnosis, especially among vulnerable populations and/or those living in remote areas. The aim of this study was to evaluate the performance of RTs for the detection of hepatitis B virus surface antigen (HBsAg) in samples from different populations/settings.MethodsThree RTs for HBsAg detection (Vikia® HBsAg, HBsAg Teste Rápido®, and Imuno-Rápido HBsAg®) and different biological specimens (serum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
2
26
0
Order By: Relevance
“…On the other hand, the confidence intervals we found for sensitivity and positive predictive value (PPV) varied widely. Similar data were found by Cruz et al 14 in their study comparing groups of patients with low and high risk of HBV infection, without CKD.…”
Section: Discussionsupporting
confidence: 89%
“…On the other hand, the confidence intervals we found for sensitivity and positive predictive value (PPV) varied widely. Similar data were found by Cruz et al 14 in their study comparing groups of patients with low and high risk of HBV infection, without CKD.…”
Section: Discussionsupporting
confidence: 89%
“…While population prevalence should not alter sensitivity of a test, a study in Brazil demonstrated that the sensitivity of a rapid diagnostic HBsAg test was 93%‐96% in a group attending a hepatitis clinic, 60% in the general population including underserved and remote communities and 67% in a vulnerable population consisting of beauticians and those who used crack cocaine . This could reflect differences in concentration of HBsAg of the three groups and has implications for our study in that our sample population may have included more patients with higher HBsAg concentrations than our overall target population . Notably, the two false negatives in our study had very low corresponding HBsAg titres and this suggests a limit of detection (Figure ).…”
Section: Discussionmentioning
confidence: 69%
“…In addition, the influence of HTLV‐1 co‐infection, endemic in Central Australia, is not known. False negatives have also occurred with syphilis co‐infection and while there is a current outbreak of syphilis among Indigenous Australians in northern and central Australia, test performance remained acceptable . Low levels of HBsAg, alanine aminotransferase level and viral load, and differing genotypes can also hinder test performance .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations